2022
DOI: 10.1101/2022.09.28.509958
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Tetraose steroidal glycoalkaloids from potato provide resistance againstAlternaria solaniand Colorado potato beetle

Abstract: Plants with innate disease and pest resistance can contribute to more sustainable agriculture. Resistance breeding typically relies on the use of immune receptors or impaired susceptibility genes, but these come with challenges in terms of strength, durability or pleotropic effects. Natural defence compounds from plants are not considered in breeding, because biosynthesis of these compounds is a complex trait and proof of their role in resistance is often indirect. Here, we identified a wild relative of potato… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 139 publications
0
3
0
Order By: Relevance
“…They found that lysophosphatidylcholine (LPC17:1) was accumulating on the surface of the wild potato, but not on S. bulbocastanum and in vitro assays revealed an antifungal activity against P. infestans (Gorzolka et al, 2021). SM associated with resistance were also the focus of another recent study in Solanum commersonii ; the differences between accessions that are resistant against A. solani and those that are susceptible can be explained by differences in glycosyltransferase genes that are involved in the production of tetraose steroidal glycoalkaloids that are toxic to A. solani (Wolters et al, 2023). In this study, we investigate the potential SMs that may play a role in the resistance of cultivated tomato plants against A. alternata .…”
Section: Discussionmentioning
confidence: 99%
“…They found that lysophosphatidylcholine (LPC17:1) was accumulating on the surface of the wild potato, but not on S. bulbocastanum and in vitro assays revealed an antifungal activity against P. infestans (Gorzolka et al, 2021). SM associated with resistance were also the focus of another recent study in Solanum commersonii ; the differences between accessions that are resistant against A. solani and those that are susceptible can be explained by differences in glycosyltransferase genes that are involved in the production of tetraose steroidal glycoalkaloids that are toxic to A. solani (Wolters et al, 2023). In this study, we investigate the potential SMs that may play a role in the resistance of cultivated tomato plants against A. alternata .…”
Section: Discussionmentioning
confidence: 99%
“…They found that lysophosphatidylcholine (LPC17:1) was accumulating on the surface of the wild potato, but not on S. bulbocastanum and in vitro assays revealed an antifungal activity against P. infestans (Gorzolka et al, 2021). Secondary metabolites associated with recentance were also focus of another recent study in S. commersonii; the differences between accessions that are resistant against A. solani and those that are susceptible, can be explained by differences in glycosyltransferase genes that are involved in the production of tetraose steroidal glycoalkaloids that are toxic to A. solani (Wolters et al, 2023). In this study, we investigate the potential SMs that may play a role in the resistance of cultivated tomato plants against A. alternata.…”
Section: Discussionmentioning
confidence: 99%
“…are capable of (Hoyos et al, 2023), implying the existence of more SGAs and other compounds in MeJA-treated leaf extracts. Wild solanaceous plants are a veritable wellspring of antifungal SGAs, with broad-spectrum antifungal tetraose SGAs conferring immunity to Solanum commersonii from EBDC (Wolters et al, 2023). This EBDC resistance locus has been successfully backcrossed into potato cultivars and confers broad resistance, also to other pathogens (Wolters et al, 2021), but the effects of tetraose SGAs to the environment and human ingestion are currently unknown.…”
Section: Hos T Defen Cementioning
confidence: 99%